The benefits of applying Kahoot media in modern EFL teaching-learning contexts - Wijaya, Kristian Florensio (Erudita: Journal of English Language Teaching, 2024)
It will be more reasonable for second language teachers to be more literate concerning the optimal internalization of proper technological learning platforms in their habitual classroom activities. Previous researchers believed that with the supportive endorsement of compatible technological-based learning tools, EFL learners are willing to showcase more proactive learning participation as they continually experience a higher degree of learning enjoyment. This small-scale library study aimed to investigate the beneficial values of applying Kahoot media in modern EFL teaching-learning contexts. To that end, the researcher plotted a thematic analysis approach in analyzing the previously generated findings from 30 previous Kahoot media journal articles. By releasing this action, more understandable research outcomes can be potentially obtained since the researcher clustered all these prior results into some identical research themes. Two major research findings were drawn: (1) Kahoot media enabled EFL learners to attain thorough foreign language mastery skills, and (2) EFL learners continually experienced more positive learning nuance by activating Kahoot media. Some pertinent recommendations and commendations were suggested for the significant advancement of forthcoming studies delving more profoundly into the utilities of technological-based learning media in various EFL classroom circumstances.